TRACE‐seq: Rapid, Low‐Input, One‐Tube RNA‐seq Library Construction Based on Tagmentation of RNA/DNA Hybrids. Issue 4 (4th April 2023) - Lu, Bo; Yi, Chengqi
Abstract: Tn5 transposase has been widely used to simultaneously fragment and tag double‐stranded DNA (dsDNA) with sequencing adaptors in library construction for next‐generation sequencing. Recently, we demonstrated that Tn5 transposase also possesses tagmentation activity toward RNA/DNA hybrids, in addition to its canonical dsDNA substrates. Based on this new activity, we are able to skip multiple laborious and time‐consuming steps in traditional RNA‐seq methods, and rapid, low‐input, cost‐effective, one‐tube RNA‐seq library construction is thus enabled. The libraries constructed by Transposase‐assisted RNA/DNA hybrids Co‐tagmEntation (termed "TRACE‐seq") demonstrate excellent performance in terms of gene expression measurement and differential gene expression analysis. Here, we present detailed protocols for TRACE‐seq that will be broadly useful for the study of RNA biology and biomedical research. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Total RNA preparation Basic Protocol 2 : TRACE‐seq library construction Support Protocol : Tn5 transposome assembly